Patient blood management programs: how to spread the word? - Shoshana Revel-Vilk; Mira Naamad (BMC, 2018)
Abstract Red blood cell (RBC) transfusions save lives and improve health; however, unnecessary transfusion practice exposes patients to immediate and long-term negative consequences. Indirect consequences of unnecessary transfusions are the reduced availability of RBC units for patients who are in need. Accumulating evidence shows that restricting RBC transfusions improves outcomes and current guidelines suggest limiting RBC transfusion to the minimum number of units required to relieve symptoms of anemia or to return the patient to a safe hemoglobin range (7-8 g/dl in stable, non-cardiac inpatients). Still, studies show that there is over-utilization of RBC transfusion, partly due to low level of knowledge of physicians regarding restrictive RBC transfusion policy across a broad range of professions and specialties. Patient blood management (PBM) programs have been developed to promote clear hospital transfusion guidelines, strive for optimization of patient hemoglobin and iron stores and, most importantly, improve education regarding restrictive RBC policy. Understanding what and where the gaps of knowledge are, as was done in the study by Dr. Koren and his colleagues, is an important step for developing effective PBM programs.